Os impactos arquitetônicos e urbanísticos do programa PROSAMIM na paisagem de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
This paper presents a literature on "Impacts of the Programme in architectural and urban landscape PROSAMIM in Manaus. Investigates the documentary and bibliographic databases through the speeches of its agents creators and implementers to address architectural and urban impacts caused by the intervention program in the city landscape and changes in function of these interventions building on a new context of housing and urban defined by public policy in Manaus. To analyze the concept, features and sectors housing along with the techniques developed in the architecture design, implemented by the Program PROSAMIM; check to what extent the PROSAMIM can help reverse the state of imbalance in the city of Manaus city, including the process spatial organization caused by the implementation.
Keywords: Paisagem natural e artificial; Impacto arquitetônico e urbanístico; PROSAMIM; Artificial and natural landscape; Architectural and urban impact; Planejamento urbano; Urban planning; OUTROS